PiyushTheorem

PiyushTheorem: In a Right-Angled Triangle with sides in A.P. Series, the distance between the point of intersection of median & altitude at the base is 1/10 Th the sum of other two sides. This Theorem applies in Two Conditions:

1.The Triangle must be Right-Angled.

2.Its Sides are in A.P. Series.

1.Proof with Trigonometry

Tan  α   =AD/DC AD= DC Tan  α   —————–1 Tan  α = AD/DE AD= DE Tan2 α   —————-2 DC Tan  α = DE Tan 2 α (DE+EC)  Tan  α = DE Tan 2 α DE Tan  α  + EC Tan  α = DE Tan 2 α DE Tan  α  + EC Tan  α = 2 DE Tan  α / (1- Tan2  α   ) DE Tan  α   – DE Tan3  α + EC Tan  α –EC Tan3  α  = 2DE Tan  α EC Tan  α –EC Tan3  α – DE Tan3  α = 2DE Tan  α – DE Tan  α Tan  α (EC – EC Tan2  α – DE T an2  α )= DE Tan  α DE Tan2  α  – DE = EC Tan2  α  – EC -DE ( Tan2  α + 1) = -EC (1 – Tan2  α ) DE (sin2 α  /cos2 α + 1) = EC (1- sin2 α  /cos2 α ) DE (sin2 α + cos2 α /cos2 α ) = EC (cos2 α – sin2 α /cos2 α ) DE (sin2 α  + cos2 α ) = EC(cos2 α  –sin2 α ) DE (sin2 α  + cos2 α ) = EC (cos2 α  –sin2 α )           where (sin2 α  + cos2 α =1) & (cos2 α  –sin2 α = cos2 α  )              DE= EC cos2 α   cos α   =a/a+d   & sin α = (a-d)/ (a +d) cos2 α  = a2/ (a +b) 2 sin2 α  = (a-d) 2/ (a+ d) 2 DE= EC (cos2 α    – sin2 α ) = EC (a2 / (a +b) 2 – (a-d) 2/ (a +d) 2 = EC (a2 – (a-d) 2/ (a +d) 2 = EC (a –a +d) (a+ a-d)/ (a+ d) 2 = EC (d) (2a -d)/ (a+ d) 2 = (a +d)/2(d) (2a -d)/ (a +d) 2 ————- where EC= (a +d)/2 = (d) (2a -d)/2(a +d) = (d) (8d -d)/2(4d+d)       ——————where a= 4d (as per the Theorem) = 7d2 /2(5d) = 7d /10 = (3d+4d)/10= (AB+AC)/10

2.Proof with Obtuse Triangle Theorem

AC2=EC2 +AE2 +2CE.DE       where EC = (  a +d) /2,AE=( a +d)/2 a2 = (a +d/2)2 + (a+ d/2)2 + 2(a +d)/2DE = (a +d/2) (a+d+2DE) = (a +d/2) (a+d+2DE)   where a=4d 16d2 = (5d/2) (5d+2DE) 32d/5 = 5d + 2DE 32d/5 – 5d = 2DE 32d -25d/5 = 2DE DE =7d/10 = (3d+4d)/10 = (AB+AC)/10

3.Proof with Acute Triangle Theorem

AB2= AC2+BC2 – 2BC.DC (a-d) 2= a2 + (a+ d) 2 -2(a+ d) (DE+EC)         where AB= (a-d), AC=a, BC =( a +d) & EC= (a +d)/2 (a-d) 2 – (a +d)2 = a2  -2(a +d)(DE+EC) (a- d –a-d) (a -d +a +d)  = a2 -2(a+ d) (2DE+a+d)/2 2(-2d) (2a) = 2a2 -2(a +d) (2DE+a+d) -8ad – 2a2 = -2(a +d) (2DE+a+d) -2a (4d   +a) = -2(a +d) (2DE+a+d) a (4d  + a) = (a +d)(2DE+a+d) 4d (4 d + 4d) = (4d+d) (2DE+4d+d) 4d (8d) = (5d) (2DE+5d) 32d2/5d =   (2DE+5d) 32d/5 =   (2DE+5d) 32d/5 – 5d =   2DE (32d – 25d)/5 =   2 DE DE = 7d/10 = (3d+4d)/10 = (AB+AC)/10

4. Proof with Co-ordinates Geometry

Equation of BE Y – 0 =b-0/0-a(X – a) Y = -b/a(X) + b——————- (1) M1 = -b/a For perpendicular M1M2= -1 So M2=a/b Equation of AC Y – 0 = a/b(X-0) Y=a/b(X) —————— (2) Put Y value in equation (1) a/b(X) + b/a(X) =b X (a2+b2/a b) = b X = ab2/ (a2 + b2) To get Value of Y, put X value in equation (2) Y = a/b (ab2/ (a2+b2) Y = a2b/ (a2+b2) Here we got co-ordinates of Point C – ab2/ (a2 + b2), a2b/ (a2+b2) and co-ordinates of point d is (a/2, b/2) because d is midpoint. As per the “Theorem” a=z-d, b=z, c = z+ d (z +d) 2= (z-d) 2+z2 from here z=4d so a=3d and b=4d Put value of a & b ab2/ (a2 + b2), a2b/ (a2+b2) & (a/2, b/2) ab2/ (a2 + b2) = 48d/25 a2b/ (a2+b2) = 36d/25 a/ 2=3d/2 b/ 2 =4d/2 CD2= (48d/25 -3d/2)2-(36d/25-4d/2)2 = (96d-75d/50)2 + (72d-100d/50)2 = (21d/50)2 + (-28d/50)2 = (441d2/2500) + (784d2/2500) = (1225d2/2500) CD= 35d/50 = 7d/10 = 7d/10 = (3d+4d)/10 = (AB+AE)/10

https://piyushtheorem.wordpress.com/2017/02/08/a-theorem-on-right-angled-triangles/

Himesh Bhai

Himesh Bhai Creator

(No description available)

Suggested Creators

Yogendra Singh

Yogendra Singh

(No description available)

Sai Kumar Gorantla

Sai Kumar Gorantla

(No description available)

Udit Kumar

Udit Kumar

(No description available)

Himesh Bhai